A simple Lewis acid induced reaction of phenols with electrophiles: Synthesis of functionalized 4H-chromenes and ortho-benzylphenols. Issue 1 (2nd January 2020) - Sreenivasulu, Chinnabattigalla; Thadathil, Ditto Abraham; Pal, Sumit; Gedu, Satyanarayana
Abstract: Lewis acid ZnCl2 promoted cyclization protocol to 4 H -chromenes is accomplished, using readily available phenols and acetophenones as starting materials. Interestingly, the process is feasible under the solvent free environment. Synthesis of a variety of 4 H -chromenes have been accomplished using this strategy. In addition, this concept is extended to the synthesis of ortho -benzylphenols by treating phenols either with styrenes or secondary benzylic alcohols. Graphical Abstract: